Intraspecific diversity and distribution of the cosmopolitan species Pseudo‐nitzschia pungens (Bacillariophyceae): morphology, genetics, and ecophysiology of the three clades. Issue 1 (20th January 2015) - Kim, Jin Ho; Park, Bum Soo; Kim, Joo‐Hwan; Wang, Pengbin; Han, Myung‐Soo; Cock, M.
<x xml:space="preserve">Abstract</x> Three clades of Pseudo‐nitzschia pungens, determined by the internal transcribed space (ITS) region, are distributed throughout the world. We studied 15 P. pungens clones from various geographical locations and confirmed the existence of the three clades within P. pungens, based on ITS sequencing and described the three subgroups (IIIaa, IIIab, and IIIb) of clade III. Clade III (clade IIIaa) populations were reported for the first time in Korean coastal waters and the East China Sea. In morphometric analysis, we found the ultrastructural differences in the number of fibulae, striae, and poroids that separate the three clades. We carried out physiological tests on nine clones belonging to the three clades growing under various culture conditions. In temperature tests, only clade III clones could not grow at lower temperatures (10°C and 15°C), although clade I and II clones grew well. The estimated optimal growth range of clade I clones was wider than that of clades II and III. Clade II clones were considered to be adapted to lower temperatures and clade III to higher temperatures. In salinity tests, clade II and III clones did not grow well at a salinity of 40. Clade I clones were regarded as euryhaline and clade II and III clones were stenohaline. This supports the hypothesis that P. pungens clades have different ecophysiological characteristics based on their habitats. Our data show that physiological and morphological features are correlated with genetic intraspecific differentiation in P. pungens.